Value of Peak Cough Flow (PCF) in Healthy Middle Adulthood and Late Adulthood and the Affecting Factors - Nury Nusdwinuringtyas; Roy Dwi Indra; Tresia Fransiska Ulianna Tambunan; Aria Kekalih (Indonesian Journal of Physical Medicine & Rehabilitation, 2020)
ABSTRACTIntroduction: Cough is a symptom that is felt by all humans and it is important for the protection which maintains mucus secretion, foreign substances, and infections of the larynx, trachea and bronchi. Thepurpose of this study is to find out the PCF value in healthy middle adulthood and late adulthood and the factors that influence it.Methods: This study is a cross-sectional study involving 99 subjects. Subjects were patients in the clinic for medical rehabilitation of middle adulthood and late adulthood healthy respiration. Subjects whofulfilled the inclusion and exclusion criteria were examined with spirometry to ensure healthy respiration and after that, the PCF examination was carried out with a peakflowmeter device and the correlation wasobserved with age, gender and, height. Results: The PCF value in healthy middle adulthood is 190-540 L / minute (41-50 years 465 L / minute, ages 51-60 years 405 L / minute) and healthy late adulthood is 245-520 L / minute with median 352.5L / minute. Men have a greater PCF value than women, but at the age of 61 years and over there not significantly different. The higher age, the lower the PCF value obtained and there was a statisticallysignificant decrease in the PCF value at 61-70 years of age compared to 41-50 years of age. Subjects with high height have a tendency for a lar ger PCF value and height will af fect the PCF value. Conclusion: Obtained PCF values in middle adulthood and late adulthood with healthy respiration and there is a relationship between sex, age and height factors for the PCF value. Keywords: Age, height, Peak Cough Flow, peakflow meter, sex.